A lock-in-based method to examine the thermal signatures of magnetic nanoparticles in the liquid, solid and aggregated states. Issue 27 (24th June 2016) - Monnier, C. A.; Lattuada, M.; Burnand, D.; Crippa, F.; Martinez-Garcia, J. C.; Hirt, A. M.; Rothen-Rutishauser, B.; Bonmarin, M.; Petri-Fink, A.
Abstract : We propose a new methodology based on lock-in thermography to rapidly and objectively quantify the heating power of magnetic nanoparticles. Abstract : We propose a new methodology based on lock-in thermography to study and quantify the heating power of magnetic nanoparticles. Superparamagnetic iron oxide nanoparticles exposed to a modulated alternating magnetic field were used as model materials to demonstrate the potency of the system. Both quantitative and qualitative information on their respective heating power was extracted at high thermal resolutions under increasingly complex conditions, including nanoparticles in the liquid, solid and aggregated states. Compared to conventional techniques, this approach offers a fast, sensitive and non-intrusive alternative to investigate multiple and dilute specimens simultaneously, which is essential for optimizing and accelerating screening procedures and comparative studies.